Utilização do zoneamento ambiental e produtivo para identificação de potencialidades e limitações de uso na bacia do Rio São Francisco Verdadeiro – PR - Perdoná, Patrícia Antonio De Oliveira (2024)
The understanding of the potentialities and limitations of the environment are extremely important in planning and decision-making processes involving the management of natural resources and the execution of human activities. And the greater the level of detail and the wealth of information about the capacity of the territorial unit of the river basins, the greater will be the possibility to build a management model on the potential for land use and water resource management. The study aims to apply the methodology of Environmental and Productive Zoning (EPZ) in the basin of the São Francisco Verdadeiro River (BSFVR). The EPZ consists of a set of information on the natural and productive environment, and is based on the elaboration of three stages: mapping of land use; calculation of water pressure by stretch of river, which considers the flow available per stretch of river and data on water use by surface allocation; and the step of delimitation of homogenies units by Conservation Use Potential (CUP), in which weights are assigned to the geology classes, soils and slope, and the potential is classified into five classes, ranging from Very Low to Very High potential. In this study, besides considering the natural potential obtained by EPZ method, scenarios of alteration of the natural potential were created considering the change in physical quality of soils, evaluated here, by soil density (SD). This is because, considering the erosion and soil loss processes in the basin, this thesis has as hypothesis that BRSVF has mostly biophysical characteristics that guarantee high potential of use, However, intensive use and sometimes with inappropriate practices has altered this natural potential. For this, studies were carried out in office, field and laboratory. In office, the necessary information was raised and generated the cartographic products, of the biophysical conditions of the area, and of flow regionalization by stretch of river. In the field, in three experimental areas in the basin (A1, A2 and A3), morphological descriptions and physical data collection of the soil were made, SD by volumetric rings (0-5 cm), penetration resistance (PR) with penetrometer, and infiltration by Guelph permeameter. In the laboratory, the granulometry and soil density were determined. The soil density data in the areas collected were used to evaluate the degree of surface compaction by intensive use and establish scenarios of change of natural potential as SD change. Samples of SD and PR were also collected at 14 random points in the basin in native vegetation, in order to evaluate the natural condition of the soils. The results indicate that the PUC classes Very Low, Low and Medium cover, respectively, 0.5%, 12.5% and 13.5% of the basin area. These classes basically reflect conditions of greater dissection of the relief and little pedogeneized soils. The potential for use High and Very High are predominant and cover about 75% of the basin area, and are associated with a gentle undulating relief, deep soils, well drained and pedogenetically developed. The use and occupancy verified, is compatible with the natural potential suggested of use. However, in the three sample areas was verified alteration in the physical quality of soils with compacted layer. The surface SD reached 1.77 g/cm³ in A1, while the limit of SD suggested in the literature for clay soils varies from 1.30 to 1.45 g/cm³. The PR in five points of the A1 did not exceed 7cm depth, and received force above 2Mpa, suggested limit for PR. Differently, data collected in the vegetation showed a SD of 0.65 g/cm³, and an average of 0.83 g/cm³, whose value is in the ideal density condition. The change scenarios showed that from SD between 1.02 and 1.13 g/cm³, i.e., the change band 3, no longer occur in the basin the classes of High and Very High potential. This means a loss of approximately 93% of potential areas in the basin. Although the results of the Water Pressure are favorable, where 99% of the water stretches are at level 1 of pressure, this is demand less than 30% of Q95, the alteration of the physical quality of the soil prevents the proper percolation inside the soil profile and interfere in the water recharge of the basin.